2000
DOI: 10.1038/sj.ejhg.5200448
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of a branch-point consensus sequence in the LMX1B gene causes exon skipping in a family with nail patella syndrome

Abstract: Nail patella syndrome (NPS) has been shown to result from loss of function mutations within the transcription factor LMX1B. In a large NPS family a 17bp intronic deletion encompassing a consensus branchpoint sequence was observed to segregate with the NPS phenotype. RNA analysis demonstrated that deletion of the branchpoint sequence resulted in skipping of the downstream exon. A mechanism to explain this phenomenon is presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…4) (this article; [1,29,40,41,63,64,65,66]). Here, we present three new LMX1B mutations, including the mutation (V240D) identified in the female patient with rapid progression of kidney disease described above (Fig.…”
Section: Lmx1b Mutations In Nps and Their Putative Effectmentioning
confidence: 96%
“…4) (this article; [1,29,40,41,63,64,65,66]). Here, we present three new LMX1B mutations, including the mutation (V240D) identified in the female patient with rapid progression of kidney disease described above (Fig.…”
Section: Lmx1b Mutations In Nps and Their Putative Effectmentioning
confidence: 96%
“…In addition, a 17 bp intronic deletion was detected in one NPS family and balanced translocations, presumably disrupting LMX1B have been reported. 11,12 Linkage studies in NPS families did not reveal evidence for locus heterogeneity thus far. Molecular studies in Lmx1b null mice modelling the NPS phenotype have proven to be pivotal to our understanding of the role of Lmx1b in the normal and disrupted development of dorsal limb structures, the kidney, the eye, and the central nervous system, and particularly focussed on the pathogenesis underlying glomerulopathy in the past decade.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, the presence of two regions of reduced variation from À23 through À27 and À35 through À39 suggests the localization of functionally important sequences from nucleotide positions À23 through À32 and À35 through À44 (e.g., the branch site). Next, we examined 46 intron sequences with experimentally determined branch site locations (Ruskin et al 1984(Ruskin et al , 1985Zeitlin and Efstratiadis 1984;Padgett et al 1985;Reed and Maniatis 1985;Hornig et al 1986;Harmuth and Barta 1988;Kuivenhoven et al 1996;Query et al 1997;Gozani et al 1998;Hamlington et al 2000;Ast et al 2001;Khan et al 2004;Kralovicova et al 2004;Kol et al 2005;Vivenza et al 2006;Vuillaumier-Barrot et al 2006) and found that the average position of the branch site adenosine is at position À26, which is consistent with the region from À23 through À32 harboring branch site sequences.…”
Section: Splice Sitementioning
confidence: 60%